Thermal inactivation of COVID‐19 specimens improves RNA quality and quantity. Issue 7 (11th December 2020) - Hemati, Maral; Soosanabadi, Mohsen; Ghorashi, Tahereh; Ghaffari, Hadi; Vahedi, Azadeh; Sabbaghian, Elaheh; Rasouli Nejad, Zahra; Salati, Amir; Danaei, Navid; Kokhaei, Parviz
Abstract: The rapid spread of coronavirus disease 2019 (COVID‐19), a disease caused by severe acute respiratory syndrome coronavirus 2, poses a huge demand for immediate diagnosis. Real‐time reverse transcriptase‐polymerase chain reaction (rRT‐PCR) of nasopharyngeal (NP) and oropharyngeal (OP) swabs have been used to confirm the clinical diagnosis. To avoid the risk of viral‐exposure of laboratory workers, thermal inactivation is currently recommended but has unknown effects on the accuracy of the rRT‐PCR results. Thirty‐six NP/OP specimens were collected from COVID‐19 patients and subjected to thermal inactivation (60°C for 30 min) or the RNA extraction processes to activate the form. Here, our data showed that the concentration of extracted‐RNA increases upon thermal inactivation compared to the active form ( p  = .028).  Significantly higher levels of RNA copy number were obtained in inactivated compared to the active samples for both N and ORF1ab genes ( p  = .009, p  = .032, respectively). Thermal inactivation elevated concentration and copy number of extracted‐RNA, possibly through viral‐capsid degradation and/or nucleoprotein denaturation. Abstract : Coronavirus disease 2019, as the novel coronavirus disease caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) with a rapid outbreak at the end of 2019, is a global health emergency. Thermal inactivation (60°C for 30 min) in the case of SARS‐CoV‐2 extracted‐RNA enhanced quality and quantity based on the extracted‐RNA concentration and reverse real‐time polymerase chain reaction results. Thermal inactivation (60°C for 30 min) may lead to designing accurate and safe protocols for virus laboratory diagnosis.